2019
DOI: 10.3389/fmicb.2019.00221
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro Evaluation of BACT/ALERT® VIRTUO®, BACT/ALERT 3D®, and BACTEC™ FX Automated Blood Culture Systems for Detection of Microbial Pathogens Using Simulated Human Blood Samples

Abstract: Blood culture (BC) is still the standard for diagnosing bloodstream infections (BSIs), especially those caused by bacteria and fungi. Infection-complicating sepsis or septic shock often occurs at BSI onset, making necessary to improve the diagnostic yield of positive BCs. Among the BC systems currently available, the BACT/ALERT® VIRTUO® (VIRTUO) system has been developed to shorten time to detection (TTD) of positive BCs. In this study, we assessed TTD for 330 clinically relevant species including 14 Gram-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…TTD was also compared between the BacT/Alert and Bactec bottles in their respective systems. For all isolates tested in the absence of any antibiotic concentrations (i.e., control bottles), TTD was faster for the BacT/Alert bottles in the Virtuo system, which is consistent with previous studies (21). These observations carried over to the antibioticcontaining bottles, where TTD was significantly shorter for BacT/Alert bottles when inoculated with E. coli and K. pneumoniae.…”
Section: Discussionsupporting
confidence: 90%
“…TTD was also compared between the BacT/Alert and Bactec bottles in their respective systems. For all isolates tested in the absence of any antibiotic concentrations (i.e., control bottles), TTD was faster for the BacT/Alert bottles in the Virtuo system, which is consistent with previous studies (21). These observations carried over to the antibioticcontaining bottles, where TTD was significantly shorter for BacT/Alert bottles when inoculated with E. coli and K. pneumoniae.…”
Section: Discussionsupporting
confidence: 90%
“…Before testing, the bacterial strains were subcultured twice overnight on standard solid media at 37°C, and their MICs were determined with the broth microdilution method according to the ISO 20776-1/2006 procedure as recommended by EUCAST (18). In our BC simulation model (19), each bottle was spiked with 8-ml banked whole blood (obtained from the Division of Transfusion Medicine at our institution), 0.5-ml antibiotic solution (obtained as described above), and 0.5-ml bacterial suspension (50 to 100 CFU, achieved after diluting a suspension of ϳ5 ϫ 10 8 CFU/ml in phosphate-buffered saline). Resins are equally useful in the presence of lower and higher microbe quantities, as those present in blood during BSIs (20), but we decided on a more stringent experimental approach and used only one inoculum in the study.…”
mentioning
confidence: 99%
“…Although all 3 systems flagged positive for 99.6% of all cultures, the median time to positivity for the BacT/ALERT VIRTUO was significant shorter. 28 A previous study comparing the BacT/ALERT 3D and VersaTREK using patient specimens found no overall difference in time to positivity or isolation of microorganisms, but there was a higher false-positive rate with the VersaTREK system (ie, 1.6% vs 0.7% for aerobic bottles). 29 However, the VersaTREK demonstrated a statistically significant higher recovery of streptococci and enterococci.…”
Section: Blood Culture Systems and Alternative Blood Culturing Methodsmentioning
confidence: 89%